OBTAINING MELON AND WATERMELON CONCENTRATES - N. S. Khanzharov (Алматы технологиялық университетінің хабаршысы, 2021)
The article is devoted to solve the issue of increasing of efficiency of using of local cucurbits crops. It is offered to obtain melon and watermelon concentrates and then to apply them as additives to confectionery products, desserts, ice-cream. There is review of scientific investigations in processing of melon and watermelon is conducted. Cucurbits crops (melon and watermelon) have high food value and complex of biological active substances, they possess by therapeutic action on human organism. Technology of concentrates from melon and watermelon is developed. Their sensory indicators and physical-chemical composition are determined in laboratory conditions. Melon and watermelon consumption rates to produce concentrates are defined. Due to sweet taste of the melon and watermelon concentrates quantity of sugar in a receipt of confectionery products, desserts, ice-cream may be decreased.